2022
DOI: 10.1021/acs.jpca.2c06149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duschinskii Rotations on Spin-Dependent Electron Transfer Dynamics

Abstract: We investigate spin-dependent electron transfer in the presence of a Duschinskii rotation. In particular, we propagate dynamics for a two-level model system for which spin–orbit coupling introduces an interstate coupling of the form e iWx , which is both position(x)-dependent and complex-valued. We demonstrate that two-level systems coupled to Brownian oscillators with Duschinskii rotations (and thus entangled normal modes) can produce marked increases in transient spin polarization relative to two-level syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…It should be pointed out that the Berry force or Berry phase has already been proposed to work as an effective way to understand the CISS effect. Recently, Dr. Subotnik and collaborators put forward that Berry force produced by the electronic–nuclear dynamics in molecules may dramatically change the pathway section of the electrons with various spin angular momenta, resulting in a remarkable spin selectivity even as the SOC is very small. , Interestingly, our theoretical results also support that the Berry phase may play a crucial role in generating the PCISS currents in CHMs. However, the underlying mechanism for the Berry phase to generate the PCISS effect is much different from the one proposed by Dr. Subotnik et al The Berry phase in our work is tightly associated with the AB effect of an external magnetic flux or an effective magnetic field induced by SOC.…”
supporting
confidence: 70%
“…It should be pointed out that the Berry force or Berry phase has already been proposed to work as an effective way to understand the CISS effect. Recently, Dr. Subotnik and collaborators put forward that Berry force produced by the electronic–nuclear dynamics in molecules may dramatically change the pathway section of the electrons with various spin angular momenta, resulting in a remarkable spin selectivity even as the SOC is very small. , Interestingly, our theoretical results also support that the Berry phase may play a crucial role in generating the PCISS currents in CHMs. However, the underlying mechanism for the Berry phase to generate the PCISS effect is much different from the one proposed by Dr. Subotnik et al The Berry phase in our work is tightly associated with the AB effect of an external magnetic flux or an effective magnetic field induced by SOC.…”
supporting
confidence: 70%
“…[1][2][3][4] These systems may provide a versatile platform for exploring the molecular origins of the chirality induced spin selectivity (CISS) effect, [5][6][7][8] without the complications of interactions with electrodes, 3,[9][10][11][12] and it has also been suggested that chiral donor-acceptor systems could be exploited in various quantum information science applications. 1,13,14 Several theories have been proposed for the molecular CISS effect and how spin polarisation is generated in the formation of charge separated states, 7,8,[15][16][17] and a handful of experimental protocols have been proposed to test these theories. 2,5,8,15,18 Whilst most studies to date have focussed on the CISS effect in the formation of charge seperated states in donor-acceptor systems, it has also been suggested that CISS could play a role in the charge recombination of donor-acceptor systems.…”
Section: Introductionmentioning
confidence: 99%